ANALISIS KEWAJIBAN PENGAWASAN NEWS PORTAL TERHADAP KOMENTAR PUBLIK DI DALAM KOLOM KOMENTAR (Studi Perbandingan Di Indonesia Dan Di Uni Eropa) - Nisa Harashta; Christine S.T. Kansil (Jurnal Hukum Adigama, 2020)
Indonesia and member countries of the European Union already recognize and have a news portal. News portals do not have a definition, but news portals are included in web portals that provide news content. Normative legal research methods. Based on the research results, if there are negative comments in the comments column on platform their, then the news portal platforms in both Indonesia and the European Union are not responsible. Both in Indonesia and in the European Union continue to monitor public comments in accordance with applicable regulations. The similarity between these two countries is that if the news portal platform continues to monitor public comments and will delete these comments, but it cannot be monitored because of the large number of incoming comments, the news portal platform provides a means to report bad comments. or deviating from the applicable rules. If after reporting to the news portal platform, it does not benefit both parties, a settlement can be made out of court or in court. Everyone who wants to comment in the comments column is free to express their opinion, by paying attention to the language used is not negative. The difference is the responsibility for the openness of public comments with the protection of Indonesia's personal data using the APEC standard Privacy Frameworks, while for the European Union it already has GDPR.